Pendekatan Teori Himpunan untuk Pemetaan Segmentasi Minat Pengguna pada Algoritma For You Page (FYP) TikTok - Abdillah, Zidan; Artika Lestari, Desti; Al Zaidan, Hilmi; Ramdhani Arrahman, Rizki; Lutfiyah, Aini; Ramadhan, Rizky; Malik Al Saleh, Sultan; Putri Zulkarnain, Nania; Sulistyani, Anjar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The massive growth of the TikTok platform is driven by the sophistication of its For You Page (FYP) algorithm, which performs real-time, interest-based content personalization. This phenomenon creates complexity in audience segmentation due to the high overlap of preferences among users. This study aims to formulate a logical-mathematical framework using Set Theory as a formal instrument to identify, map, and analyze the relationships between TikTok user interest segments through a literature review method. The modeling results show that the concepts of universal set, subset, and basic operations such as intersection, union, difference, complement, and cardinality can be effectively transformed into a precise audience segmentation model. The intersection operation identifies niche audiences, the union operation maps the accumulation of broad market reach, and the difference operation functions as an exclusion-list filtering mechanism. This study contributes theoretically through an interdisciplinary synthesis between discrete mathematics and social communication science, and practically as a strategic guide for digital marketers and content creators optimizing message-distribution targeting on social media.